2018
DOI: 10.1080/20002297.2018.1492316
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oral microbiota and acetaldehyde production

Abstract: Background: Neisseria has been reported to be a high producer of acetaldehyde (ACH), a carcinogen, from ethanol in vitro, but no information exists regarding whether the ACH production depends on oral microbiota profiles.Objective and Design: To explore the salivary microbiota profiles with respect to ACH production ability in the oral cavity using a cross-sectional design.Results: Using 16S rRNA gene amplicon sequencing, we classified 100 saliva samples into two types of communities (I and II). Salivary ACH p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Therefore, Neisseria species might be associated with DTC due to the production of acetaldehyde in the oral cavity after alcohol consumption. However, our previous study suggested that their phenotypes in vitro do not necessarily reflect their behavior in vivo because of interactions in the bacterial community (Yokoyama et al, 2018). To elucidate the acetaldehyde-mediated carcinogenesis, further comprehensive studies of these Neisseria species in vitro and in vivo are required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Neisseria species might be associated with DTC due to the production of acetaldehyde in the oral cavity after alcohol consumption. However, our previous study suggested that their phenotypes in vitro do not necessarily reflect their behavior in vivo because of interactions in the bacterial community (Yokoyama et al, 2018). To elucidate the acetaldehyde-mediated carcinogenesis, further comprehensive studies of these Neisseria species in vitro and in vivo are required.…”
Section: Discussionmentioning
confidence: 99%
“…Individual characteristics of thousands of different microbial strains play a key role in the regulation of salivary ACH concentrations in the presence of ethanol (Table 3). Based on 100 saliva samples of healthy volunteers, a 30-fold range in the ability of oral microbes to produce ACH from ethanol has been demonstrated [21]. This explains at least in part the high individual variation in salivary ACH concentrations after alcohol ingestion.…”
Section: Major Factors Affecting Salivary Ach Levelsmentioning
confidence: 98%
“…Neisseria species are highly abundant in the human oral cavity and have been detected in, for instance, saliva, plaque, mucosal surfaces in the mouth, and teeth, and Neisseria has been regarded as part of the ''core microbiome'' of the healthy human oral cavity (Keijser et al, 2008;Zaura et al, 2009). It has previously been shown that Neisseria is able to produce the carcinogenic organic compound acetaldehyde; however, it is not clear if in vivo production of acetaldehyde by Neisseria is related to carcinogenesis (Muto et al, 2000;Yokoyama et al, 2018 Article gammaherpesvirus are all related to the oral cavity, and some are implicated in oral cancer or oral leukoplakia.…”
Section: Discussionmentioning
confidence: 99%